The level of conservatism and earnings management during IFRS adoption - Yie Ke Feliana; Jessica Bagus (University of Merdeka Malang, 2020)
We analysis to determine the level of conservatism and earnings management in the period of IFRS adoption in Indonesia. We used a quantitative approach and was tested using a different group test, i.e. Mann-Whitney U, ANOVA, and MANOVA. The object of this research is all manufacturing companies listed in Indonesia Stock Exchange (IDX) for the period of 2012-2017. The number of samples used in this research is 516 firm-years. Earnings management is measured by two approaches, i.e. accrual earnings management and real earnings management, while conservatism is measured by Basu Model. The level of conservatism and earnings management in this study focuses on after the IFRS adoption period. We reveal that IFRS adoption does not change accounting conservatism in financial statements. In addition, the greater adoption of IFRS is not able to reduce the level of overall earnings management both in accrual earnings management and real earnings management.JEL Classification: C33, M41, G02 How to Cite:Feliana, Y. K., Bagus, J. (2020). The level of conservatism and earnings management during IFRS adoption. Jurnal Keuangan dan Perbankan, 24(1), 53-67.DOI: https://doi.org/10.26905/jkdp.v24i1.3294